STRATEGI SEKOLAH DALAM PENINGKATAN PESERTA DIDIK BARU (STUDI KASUS SMA LABSCHOOL UNESA 1) - Maruta Pradana, Ramadhan; Murtadlo, Murtadlo; Widodo, Bambang Sigit (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
The emergence of private schools in urban areas is to fill the lack of availability of public schools because the population is not balanced with the number of schools. The mushrooming of private schools raises new problems in getting students in uncertain conditions. Many private schools do not get students or do not fit the class, which makes these private schools have to be closed. SMA Lab School UNESA 1 has a strategy used to increase the number of students in each new school year. The purpose of this research is to see how the school's efforts to increase the number of students in the new school year. In this study using a qualitative case study method, data collection techniques were used by interviews, observation, and documentation studies. The subjects in this study were the school principal, vice principal, teacher, and student guardians. Data analysis techniques with data condensation, data presentation, and data conclusions are displayed. The results of this research have three main themes, namely the school's internal strategy in improving the school's internal system, external strategies related to cooperative relations and communication carried out by school stakeholders, and the obstacles experienced can be used as a reference for future evaluations in improving school strategies. The conclusion of the strategy carried out by SMA Lab School is to improve the internal quality of the school, improve cooperative relations with externals, and pay attention to the obstacles that occur during the process of implementing the strategy in increasing the number of students in the new school year.